Unique Expression of Angiotensin Type-2 Receptor in Sex-Specific Distribution of Myelinated Ah-Type Baroreceptor Neuron Contributing to Sex-Dimorphic Neurocontrol of Circulation. Issue 4 (April 2016) - Liu, Yang; Zhou, Jia-Ying; Zhou, Yu-Hong; Wu, Di; He, Jian-Li; Han, Li-Min; Liang, Xiao-Bo; Wang, Lu-Qi; Lu, Xiao-Long; Chen, Hanying; Qiao, Guo-Fen; Shou, Weinian; et al.
Abstract : This study aims to understand the special expression patterns of angiotensin-II receptor (AT1 R and AT2 R) in nodose ganglia and nucleus of tractus solitary of baroreflex afferent pathway and their contribution in sex difference of neurocontrol of blood pressure regulation. In this regard, action potentials were recorded in baroreceptor neurons (BRNs) using whole-cell patch techniques; mRNA and protein expression of AT1 R and AT2 R in nodose ganglia and nucleus of tractus solitary were evaluated using real time–polymerase chain reaction, Western blot, and immunohistochemistry at both tissue and single-cell levels. The in vivo effects of 17β-estradiol on blood pressure and AT2 R expression were also tested. The data showed that AT2 R, rather than AT1 R, expression was higher in female than age-matched male rats. Moreover, AT2 R was downregulated in ovariectomized rats, which was restored by the administration of 17β-estradiol. Single-cell real time–polymerase chain reaction data indicated that AT2 R was uniquely expressed in Ah-type BRNs. Functional study showed that long-term administration of 17β-estradiol significantly alleviated the blood pressure increase in ovariectomized rats. Electrophysiological recordings showed that angiotensin-II treatment increased the neuroexcitability more in Ah- than C-type BRNs, whereas no such effect was observed in A-types. In addition, angiotensin-II treatment prolonged action potential duration, which was not further changed by iberiotoxin. The density of angiotensin-II–sensitive K + currents recorded in Ah-types was equivalent with iberiotoxin-sensitive component. In summary, the unique, sex- and afferent-specific expression of AT2 R was identified in Ah-type BRNs, and AT2 R-mediated KCa1.1 inhibition in Ah-type BRNs may exert great impacts on baroreflex afferent function and blood pressure regulation in females. Abstract : Supplemental Digital Content is available in the text.